Makkiyah – Madaniyah Asy Syatibi Dan Implikasinya Terhadap Pengembangan Pemikiran Islam Substantif Dan Kultural - Alamsyah, Alamsyah (Universitas Islam Negeri Raden Intan Lampung, 2020)
This writing studies Syatibi’s thought on the appropriation of both the Qur’an and Hadith of the makkiyah period as “the root” (usul) and those of the madaniyyah as “the branch” (furu’). Such thought implies the function of the makkiyah texts as “the principle”, and the madaniyah ones as “the implementation”. This paper then questions the extent to which such thought by Syatibi is relevant with the renewal of Islamic law in contemporary Muslim societies. It uses literary study as its research method, and does its data analysis qualitatively. This research finds out that, Syatibi views the makkiyah texts as an ushul that constitutes a subsistence of maqasid syariah (purposes of the law), while the madaniyah texts as a furu’, one that forms the implementation of that maqasid syairah. Using his theory of istiqrai makwani, Syatibi views the makkiyah texts as a deductive justification which consists of legal norms between human beings. The teachings of morality and ethics contained in the makkiyah justification are fixed, while those of the madaniyah justification are dynamic and contingent. The consequence is that any form of obligation and prohibition in Islamic law which are derived from the madaniyah justification is dynamic and are changing according to its spatial and historical contexts: hence the compatibility of the texts with the principle of maqasid syariah.